Utilizing the Space‐Charge Region of the FeNi‐LDH/CoP p‐n Junction to Promote Performance in Oxygen Evolution Electrocatalysis - He, Kai; Tadesse Tsega, Tsegaye; Liu, Xi; Zai, Jiantao; Li, Xin‐Hao; Liu, Xuejiao; Li, Wenhao; Ali, Nazakat; Qian, Xuefeng (Angewandte Chemie International Edition, 2019)
The modulation of electron density is an effective option for efficient alternative electrocatalysts. Here, p‐n junctions are constructed in 3D free‐standing FeNi‐LDH/CoP/carbon cloth (CC) electrode (LDH=layered double hydroxide). The positively charged FeNi‐LDH in the space‐charge region can significantly boost oxygen evolution reaction. Therefore, the j at 1.485 V (vs. RHE) of FeNi‐LDH/CoP/CC achieves ca. 10‐fold and ca. 100‐fold increases compared to those of FeNi‐LDH/CC and CoP/CC, respectively. Density functional theory calculation reveals OH− has a stronger trend to adsorb on the surface of FeNi‐LDH side in the p‐n junction compared to individual FeNi‐LDH further verifying the synergistic effect in the p‐n junction. Additionally, it represents excellent activity toward water splitting. The utilization of heterojunctions would open up an entirely new possibility to purposefully regulate the electronic structure of active sites and promote their catalytic activities. The p‐n junction in FeNi‐LDH/CoP with positively charged FeNi‐LDH in the space‐charge region exhibits superior electro‐catalytical activity for the oxygen evolution reaction (OER). LDH=layered double hydroxide.